Exclusive content and platform competition in Latin America - Cuntz, Alexander; Bergquist, Kyle (World Intellectual Property Organization, 2020)
Platforms often compete over non-price strategies such as the exclusive distribution of products. But these strategies are not always welfare-enhancing. Using rich data on audiovisuals distributed on platforms in Brazil, we find that non-exclusive distribution and availability of titles across platforms is more effective in deterring online piracy than in the single homing case. Moreover, in certain markets (TVOD), it induces higher average investment in the production of new titles upstream. We discuss options of copyright and antitrust policies in the light of these findings.
"November 2020."
Keywords: Copyright -- Latin America.; Piracy -- Latin America.; Intellectual property -- Latin America.; Copyright.; Droit d'auteur.; Droit d'auteur -- Amérique latine.; Propriété intellectuelle -- Amérique latine.; copyright.; Copyright; Piracy; Latin America